Deacidification And Decoloration (Jatropha Curcas L.) Using Membrane Microfiltration - Ika Amalia Kartika; Sri Yuliani; Dhiani Dyahjatmayanti (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
This study focused on the deacidification and decoloration of crude jatropha oil using microfiltration membrane. The experiment was conducted with hydraulic-pressed jatropha oil and polypropylene (PP) membrane hollow fiber with a molecular weight cut-off (MWCO) of 0.01 μm and a permeation area of 1 m2. Several tests were carried out to define the best performance (permeate flux, free fatty acid reduction and clarity) by studying the influence of duration and frequency of backflush. Permeate flux was low but remained stable for a long period. No long-term fouling appeared during the membrane processing. The permeate flux increased with transmembrane pressure. In addition, the backflush treatment can recover and increase permeate flux. The higher permeate flux of 8.42 l/m2.h was obtained under duration and frequency of backflush of 6 seconds and 15 times, respectively. Furthermore, microfiltration membrane was found to have a positive effect on color reduction, but was not affective for deacidification. Keyword: Microfiltration, Polypropylene, Jatropha oil, Backflush.